2012
DOI: 10.1097/mpg.0b013e3181f8b55d
|View full text |Cite
|
Sign up to set email alerts
|

Graded Compression and Power Doppler Ultrasonography Versus Endoscopy to Assess Paediatric Crohn Disease Activity Pre‐ and Posttreatment

Abstract: Results obtained using power Doppler ultrasonography and endoscopy showed statistically significant correlations. Power Doppler sonography, in the hands of an experienced examiner, can be used for follow-up assessment of disease activity in children with Crohn disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…The utility of bowel US for assessing drug response has been compared with ileocolonoscopy only in 3 studies in which concordance was high (weighted k between 0.63 and 0.76). 80,82,86 Two studies showed no changes in ultrasongraphic parameters before and after therapy. 81,87 One study demonstrated variations of a combination of sonographic parameters (sonographic lesion index for CD) only in patients with clinical response to anti-tumor necrosis factor a treatments induction.…”
Section: Monitoring Therapeutic Responsesmentioning
confidence: 95%
See 1 more Smart Citation
“…The utility of bowel US for assessing drug response has been compared with ileocolonoscopy only in 3 studies in which concordance was high (weighted k between 0.63 and 0.76). 80,82,86 Two studies showed no changes in ultrasongraphic parameters before and after therapy. 81,87 One study demonstrated variations of a combination of sonographic parameters (sonographic lesion index for CD) only in patients with clinical response to anti-tumor necrosis factor a treatments induction.…”
Section: Monitoring Therapeutic Responsesmentioning
confidence: 95%
“…Nine studies including 265 patients with CD, have explored the evolution of sonographic parameters of inflammation over time during medical therapy [80][81][82][83][84][85][86][87][88] (see Table 11, Supplemental Digital Content 5, http://links.lww.com/IBD/B238). The utility of bowel US for assessing drug response has been compared with ileocolonoscopy only in 3 studies in which concordance was high (weighted k between 0.63 and 0.76).…”
Section: Monitoring Therapeutic Responsesmentioning
confidence: 99%
“…More recently, several authors have suggested that ultrasonography (US) can be used for screening and follow-up of small bowel Crohn disease in children (6)(7)(8)(9)(10)(11). Technologic advances in US have allowed improved visualization of the small bowel and mesentery, especially in the pediatric population.…”
Section: Introductionmentioning
confidence: 99%
“…Technologic advances in US have allowed improved visualization of the small bowel and mesentery, especially in the pediatric population. One pediatric study ing one or more high-frequency linear transducers (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18), convex transducers with lower frequencies may be useful for visualizing bowel loops located deep within the abdomen or pelvis and for examining obese children. Graded compression of the anterior abdominal wall with the US transducer and manual posterior compression with the nonscanning hand can be used to displace or efface normal overlying air and fluid-filled bowel loops and bring abnormal bowel segments closer to the transducer for improved image quality (10,14).…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies, including a pediatric study, have used ultrasound to evaluate Crohn's disease and to monitor disease [26][27][28]. The results of these studies suggest that ultrasound can detect ileal disease and can be used to monitor improvement in disease, if there is an experience and expertise in ultrasound at an institution.…”
Section: Ultrasoundmentioning
confidence: 99%